Impact of aperture separation on wind-driven single-sided natural ventilation. (1st November 2016) - Daish, N.C.; Carrilho da Graça, G.; Linden, P.F.; Banks, D.
Abstract: This paper presents a study of the impact of horizontal aperture separation in single-sided ventilation flows with two apertures (SS2). The study is based on wind tunnel measurements and dimensional analysis. The results show that the SS2 ventilation flow rate, scaled with incoming wind velocity and aperture area, depends on the incoming wind angle relative to the aperture façade, θ, and on the aperture separation scaled by building width, s ′. For most wind angles, the ventilation flow increases as the square-root of s ′. This study also identified a novel flow driving mechanism – vortex shedding: when the ventilation openings are on the leeward side of the building and the wind is nearly head-on, the flow is driven by a pumping mechanism due to vortex shedding. Highlights: Impact of aperture separation on single-sided ventilation rate quantified. Wind direction, with high resolution (every 11.25°), also taken into account. Relative importance of mean/fluctuating pressure components explicitly considered. Realistic building geometries modelled, including sheltering effects. New single-sided ventilation mechanism – "pumping flow" due to vortex shedding.